2022
DOI: 10.3390/jcm11164753
|View full text |Cite
|
Sign up to set email alerts
|

Early Serum Creatinine Levels after Aneurysmal Subarachnoid Hemorrhage Predict Functional Neurological Outcome after 6 Months

Abstract: Acute kidney injury (AKI) is a known predictor of unfavorable outcome in patients treated at the ICU, irrespective of the disease. However, data on the potential influence of serum creatinine (sCr) on hospital admission on the outcome in patients suffering from aneurysmal subarachnoid hemorrhage (SAH) is scarce. A total of 369 consecutive patients suffering from SAH were included in this retrospective cohort study. Patients were divided into good-grade (WFNS I–III) versus poor-grade (WFNS IV–V). Outcome was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, there is limited research on the association between sCr and mortality rates in SAH patients. A previous study involving 369 SAH patients showed that patients with a sCr level ≥ 1.0 mg/dL had a higher likelihood of poorer prognosis (modified Rankin Scale score > 3) compared to SAH patients with sCr levels <1.0 mg/dL ( 11 ). These findings align with our study, which demonstrated that patients with sCr level ≥ 0.9 mg/dL had a higher mortality rate compared to those with sCr level < 0.9 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited research on the association between sCr and mortality rates in SAH patients. A previous study involving 369 SAH patients showed that patients with a sCr level ≥ 1.0 mg/dL had a higher likelihood of poorer prognosis (modified Rankin Scale score > 3) compared to SAH patients with sCr levels <1.0 mg/dL ( 11 ). These findings align with our study, which demonstrated that patients with sCr level ≥ 0.9 mg/dL had a higher mortality rate compared to those with sCr level < 0.9 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common complication in critically ill patients and SAH patients, and its negative impact on outcomes is well known ( 10 ). Although the effect of sCr on the neurological function assessment of SAH patients has been described ( 11 ), the study’s sample size was small, and there was a lack of data on mortality in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological outcome was measured using the modified Rankin Scale (mRS). If an article presented numerical data for individual mRS classes, the data were documented based on the definition of a poor outcome as a score ranging from 3 to 6 on the mRS scale, while a score ≤ 2 was considered indicative of a good outcome [ 21 ]. If a study presented the percentage of patients with a defined outcome event, the absolute numbers were computed using the provided percentages.…”
Section: Methodsmentioning
confidence: 99%
“…Modified Ranking scale was used to measure the neurological outcome, which was, subsequently, evaluated in accordance with the definition of poor outcome as a score of 3-6 and good outcome as a score of 0-2 [21]. The Markwalder grading score was dichotomized into good (0-1) and poor (2-4) outcome.…”
Section: Types Of Studiesmentioning
confidence: 99%